A Cross‐Sectional Cohort Study of the Effects of FGF23 Deficiency and Hyperphosphatemia on Dental Structures in Hyperphosphatemic Familial Tumoral Calcinosis. (22nd March 2021) - Lee, Alisa E; Chu, Emily Y; Gardner, Pamela J; Duverger, Olivier; Saikali, Amanda; Wang, Sean K; Gafni, Rachel I; Hartley, Iris R; Ten Hagen, Kelly G; Somerman, Martha J; Collins, Michael T
ABSTRACT: Hyperphosphatemic familial tumoral calcinosis (HFTC) is a rare autosomal recessive disorder caused by mutations in FGF23, GALNT3, KLOTHO, or FGF23 autoantibodies. Prominent features include high blood phosphate and calcific masses, usually adjacent to large joints. Dental defects have been reported, but not systematically described. Seventeen patients with HFTC followed at the National Institutes of Health underwent detailed clinical, biochemical, molecular, and dental analyses. Studies of teeth included intraoral photos and radiographs, high‐resolution μCT, histology, and scanning electron microscopy (SEM). A scoring system was developed to assess the severity of tooth phenotype. Pulp calcification was found in 13 of 14 evaluable patients. Short roots and midroot bulges with apical thinning were present in 12 of 13 patients. Premolars were most severely affected. μCT analyses of five HFTC teeth revealed that pulp density increased sevenfold, whereas the pulp volume decreased sevenfold in permanent HFTC teeth compared with age‐ and tooth‐matched control teeth. Histology revealed loss of the polarized odontoblast cell layer and an obliterated pulp cavity that was filled with calcified material. The SEM showed altered pulp and cementum structures, without differences in enamel or dentin structures, when compared with control teeth. This study defines the spectrum and confirms the high penetrance of dental features in HFTC. The phenotypes appear to be independent of genetic/molecular etiology, suggesting hyperphosphatemia or FGF23 deficiency may be the pathomechanistic driver, with prominent effects on root and pulp structures, consistent with a role of phosphate and/or FGF23 in tooth development. Given the early appearance and high penetrance, cognizance of HFTC‐related features may allow for earlier diagnosis and treatment. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.